A thylakoid-located carbonic anhydrase regulates CO2 uptake in the cyanobacterium Synechocystis sp. PCC 6803 - Sun, Nan (The New phytologist, 2019)
© 2018 The Authors. New Phytologist © 2018 New Phytologist Trust.